N(G)-nitro-L-arginine Methyl Ester Protects Against Hormonal Imbalances Associated with Nicotine Administration in Male Rats - Oyeyipo, Ibukun P. (N Am J Med Sci, 2015)
BACKGROUND: The administration of nicotine is associated with altered hormonal imbalances and increased serum and testicular nitric oxide (NO) level. AIM: This study sought to investigate the effects of NO inhibition with N(G)-nitro-L-arginine methyl ester (L-NAME) on altered hormonal imbalance in adult male albinorats. MATERIALS AND METHODS: Rats were administered with 0.5 mg/kg body weight (BW) and 1.0 mg/kg BW nicotine and were treated with L-NAME in the drinking water or drinking water alone for 30 days. Serum was analyzed for testosterone, luteinizing hormone (LH), follicle stimulating hormone (FSH), and prolactin using radioimmunoassay. RESULTS: Nicotine administration significantly decreased (P < 0.05) testosterone in the low and high dose treated groups and FSH in the high dose treated group when compared with the control group. There was a significant increase (P < 0.05) in mean LH and prolactin level in the high dose treated group when compared with the control. Concomitant treatment with nicotine and L-NAME produced significant increases in testosterone and FSH, and a decrease in prolactin in 1.0 mg/kg BW. L-NAME alone did not lead to a significant increase in testosterone when compared with control. CONCLUSION: These data demonstrate that the suppressive effects of nicotine on testosterone level of the adult male rat can be prevented by NOS blockade with L-NAME. It appears that these beneficial effects are mediated primarily within the gonad; however, the involvement of the pituitary cannot be totally ruled out.